2001
DOI: 10.1021/ma002101n
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Stimuli-Responsive Conjugated Polymers Having Azobenzene Units in the Main Chain

Abstract: Poly(p-phenyleneethynylene)-and heteroaromatic-containing poly(phenylene)-based conjugated polymers having photoisomerizable azobenzene units in the main chain were prepared using palladium-catalyzed cross-coupling reaction of 4,4′-diiodoazobenzenes with 1,4-diethynylbenzenes and bis(trimethylstannyl)heteroaromatics, respectively. Polymers possessing n-hexyl side chains on the aromatic rings were soluble in common organic solvents such as tetrahydrofuran, chloroform, and toluene. The polymers were thermally st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…But there is no main chain peaks in the area of 30~36 ppm. In addition, the total peak area of C 6 and C 7 equivalent to that of C 1 and C 2 , and the total area of C 9 and C 10 is as 1.8 times as C 8 . This suggests that the interaction between the acrylonitrile units and vinylpyridine units is weak.…”
Section: Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…But there is no main chain peaks in the area of 30~36 ppm. In addition, the total peak area of C 6 and C 7 equivalent to that of C 1 and C 2 , and the total area of C 9 and C 10 is as 1.8 times as C 8 . This suggests that the interaction between the acrylonitrile units and vinylpyridine units is weak.…”
Section: Characterizationmentioning
confidence: 98%
“…Presently, various azobenzene-containing materials have been exploited by doping low-molecularweight azo dyes in polymers or covalent synthesis of azo polymers including side chain [6,7], main chain [8,9], and dendrimers [10]. However, doping films usually have low azo content due to poor compatibility, and the obtained photoinduction have been proved to be temporally unstable [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no fluorescence observed, as most literature reported. [2][3][4]15,17,18 The excitation energy was consumed by the photoisomerization between trans and cis isomers for the azo compound, instead of emitting fluorescence. The monomer was found to have a sharp absorbance peaked around 350 nm, while the PPEPAPE in solution displayed a red-shifted, relatively broad absorbance with a peak around 450 nm and a shoulder around 330 nm.…”
Section: Thementioning
confidence: 99%
“…In 2010 a study showed that azobenzene containing polymers can be used as the dispersing agents for carbon nanotubes [16]. Several conjugated polymers having azobenzene unit on the backbone were reported for interesting applications such as nonlinear optical devices, self structuring polymer films and photoresponsive polymers [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%